Pemberdayaan Perempuan dalam Restorasi Keadilan Melalui Pelatihan Mediasi di Wadah Babaikan, Kecamatan Rantau Badauh: Women's Empowerment in Justice Restoration Through Mediation Training at Wadah Babaikan, Rantau Badauh District - Utami, Suci; Hanifah, Lena; Erlina, Erlina; Erniyati, Tiya; Buana, Mirza Satria; Firdaus, Muhammad Ananta; Ristiawati, Risni; Tajmila, Tajmila; Hildayanti, Hana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The gender role gap in the justice restoration process is an urgent issue that needs attention, especially in the framework of women's empowerment. Restorative justice centers on repairing relationships and restoring social balance after violations or injustices. However, in practice, especially in the Restorative Justice House of Wadah Babaikan, Rantau Badauh District, Barito Kuala Regency, South Kalimantan, women often face significant obstacles that hinder their full participation in this process. These obstacles include the low knowledge of human resources about Restorative Justice/Mediation as an alternative to dispute resolution, which impacts women's confidence and institutions in increasing the role of women in resolving legal cases peacefully, so intervention is needed to improve competence. The method used in this activity is a workshop on mediation, law, and techniques in conflict reconciliation. This workshop had a significant impact on improving the competence of resolving legal issues in their respective villages in the administrative area, as seen in the results of the post-test that knowledge and understanding related to the resolution of legal problems through mediation increased and built the confidence and competence/ability of village women in Rantau Badauh District to behave and behave in involvement during the justice restoration process in their respective areas.